Perancangan dokumen ssop pada proses produksi susu pasteurisasi menggunakan teknologi PEF di CV Milkinesia Nusantara - Nanda Fitriyatul Amalia; Teti Estiasih; Anugerah Dany Priyanto; Angky Wahyu Putranto; Widyasari Widyasari (AGROINTEK, 2024)
CV Milkinesia Nusantara is a small, medium dairy product enterprise in Ponorogo, a developing company to improve the production process. It is now focused on the production of pasteurized milk using technology that combines using pasteurization of pulsed electric field (PEF) method and is supported by semi-continuous integrated processing machines. Before starting production with the new system, CV Milkinesia Nusantara would like to establish a standardized production process plan and contamination-free. Therefore, this research aimed to evaluate the sanitation standard operating procedures (SSOP) and to create SSOP document for determining the sanitation hygiene program during the milk production. The descriptive qualitative method was used in this research, and the SSOP document's designed based on 8 key sanitation requirements adapted from literature and several related regulations. There are several adjustments in the initial proposal of the SSOP document for future implementation, which is analyzing the laboratory's water quality test once a year. In addition, the sanitation method of processing machines is changed to a combination of manual (COP) and simple Cleaning in Place (CIP) methods. Moreover, microbiological testing of food-contact surfaces is changed to once every 3 months. Utilization of cleaning equipment is distinguished by specifying color codes, and the cleaning agents for machine processing were performing the recommended COP cleaner. An additional form is provided for documenting employee training activities